2015
DOI: 10.1002/qj.2514
|View full text |Cite
|
Sign up to set email alerts
|

A scaling relation for warm‐phase orographic precipitation: a Lagrangian analysis for 2D mountains

Abstract: The precipitation produced by orographic clouds is the result of the interaction between nonlinear dynamical and microphysical processes. Focusing on warm-phase stable clouds, we propose that the precipitation efficiency is essentially controlled by the bulk Damköhler number of the system, i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Otherwise, the change in isotopic content due to temperature exceeds that due to CDNC by a factor of approximately 10 for the ranges of temperature and CDNC explored here. The weaker sensitivity of precipitation to CDNC changes with increasing precipitation is reminiscent of the work of Muhlbauer et al [] for mixed‐phase clouds and Miltenberger et al [] for warm clouds. The possibility remains that a model setup that yields weaker precipitation might show a stronger sensitivity of precipitation to CDNC changes, as in Miltenberger et al [].…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the change in isotopic content due to temperature exceeds that due to CDNC by a factor of approximately 10 for the ranges of temperature and CDNC explored here. The weaker sensitivity of precipitation to CDNC changes with increasing precipitation is reminiscent of the work of Muhlbauer et al [] for mixed‐phase clouds and Miltenberger et al [] for warm clouds. The possibility remains that a model setup that yields weaker precipitation might show a stronger sensitivity of precipitation to CDNC changes, as in Miltenberger et al [].…”
Section: Model Resultsmentioning
confidence: 99%
“…The weaker sensitivity of precipitation to CDNC changes with increasing precipitation is reminiscent of the work of Muhlbauer et al [] for mixed‐phase clouds and Miltenberger et al [] for warm clouds. The possibility remains that a model setup that yields weaker precipitation might show a stronger sensitivity of precipitation to CDNC changes, as in Miltenberger et al []. However, the change in δ18normalOnormalprecip due to CDNC is unlikely to increase far beyond the range seen in the reference case (W800m).…”
Section: Model Resultsmentioning
confidence: 99%
“…For instance, Miltenberger et al (2013) implemented online trajectories in the COSMO model, hence allowing the trajectories to take full advantage of a 20 s time step. They applied the new method particularly to problems in orographic precipitation (Miltenberger et al, 2015), but an illustrative case of a north foehn study clearly showed the potential of the new method for foehn-related studies (Miltenberger, 2014). In a systematic study, Bowman et al (2013) looked at the minimal time resolution of the input winds required in Lagrangian models.…”
Section: Introductionmentioning
confidence: 99%
“…A conceptual model of the sedimentation fluxes provides insight into the key variables controlling the modification of the moisture profile and may be used to represent these in models with a lower spatial resolution. Similar to previously proposed conceptional models for orographic precipitation Smith (1979); Smith and Barstad (2004); Seifert and Zängl (2010); Miltenberger et al (2015), we chose an ansatz based on the consideration of the characteristic timescales of the cloud:…”
mentioning
confidence: 99%